PUBLIC MANAGEMENT OF COMPETENCIES IN THE CONDITIONS OF APPLICATION OF MODERN INFORMATION AND COMMUNICATION TECHNOLOGIES - Stativka , N.; Bubliy , M. (Theory and Practice of Public Administration, 2021)
The article examines public competence management in the context of the use of modern information and communication technologies. The process of public competence management in the context of the use of modern computer technologies and software, the following should be noted. The process of public competence management should be based on the functioning of three subsystems: the management subsystem (bodies of state and municipal administration, whose competence includes making decisions that have an increased public response, and representatives of public and business structures engaged in the formation of an effective system of public control); managed subsystem (the population of a particular territory is an object of management as a carrier of knowledge); information and communication plan interaction subsystem (vertical and horizontal, forward and reverse, communication between state, society and business institutions). The involvement of the intellectual resource of the population in the process of achieving goals that have an increased public response determines the strengthening of the public nature of management. The effectiveness of public management depends on the consistency of the functioning of three subsystems of public competence management: the management subsystem, the managed subsystem, and the information and communication interaction subsystem. Based on the above, concluding that the public competence management process itself is a set of such components as competence management and the use of competencies in action, which include a set of procedures, compliance with which is necessary to obtain the desired result. The main stages of competence formation in the process of their public acquisition include: identification (definition) of competencies, acquisition of competencies, fixing competencies, using competencies in decision-making, competence development, codification, improvement and transfer (transfer) of data, analysis and expressed constructive reaction with participants in interaction, generation and preservation of competencies. Using the technological and social potential at the present stage of social development, it is possible to obtain a synergistic effect of the joint functioning of modern information technologies and the knowledge of the expert community, necessary for improving the public administration system and solving socially significant problems.